Розробка інформаційної системи покупки квитків на потяги з функцією, яка рекомендує клієнту оптимальний рейс - Сербін, О. В. (ХНУРЕ, 2024)
The work describes the development of an information system for purchasing train tickets, incorporating a feature that recommends optimal flights to the customers. The system will take into account either popular routes for a given user's destination or consider their past journeys. Additionally, it will factor in potential transfers during the trip. By analyzing these elements, the system aims to recommend the most suitable train routes to users, thereby enhancing their travel experience and satisfaction.
Keywords: покупка квитків; оптимальний рейс; інформаційна система; рекомендації рейсів; управління подорожами